Tindak Pidana Perbankan di Indonesia: Analisis Yuridis terhadap Jenis Kejahatan dan Pertanggungjawaban Pidana - Revameila Susanti; Muhammad Haidar Pasha; Teguh Abdurrohman Shodiq (Journal of Legal, Political, and Humanistic Inquiry, 2025)
This study aims to examine banking crimes in Indonesia by focusing on the classification of types of banking offenses and the forms of criminal liability that may be imposed on perpetrators. The analysis is grounded in the recognition that the banking sector plays a strategic role in the national economy, such that any legal violation in this field has the potential to cause systemic losses and undermine public trust. The research employs a normative juridical method with a statutory approach, particularly referring to Law Number 7 of 1992 as amended by Law Number 10 of 1998 on Banking. The findings indicate that banking crimes encompass acts related to licensing, bank secrecy, supervision and regulation, as well as banking business activities, each of which is subject to strict criminal sanctions. Furthermore, criminal liability is not confined to individuals but may also be imposed on corporations and their management. This study underscores the importance of consistent enforcement of banking criminal law to ensure a sound, accountable, and equitable banking system.